Dealing with the COVID-19 Pandemic in Indonesia: MSMEs’ Coping Strategy, Recovery Path, and Business Transformation - Gunadi, Ahmad Dading; Lesmana, Harry; Fachrizah, Hilda; Revindo, Mohamad Dian; Daniswara, Rama Vandika (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2022)
Since the first confirmed COVID-19 infection in Indonesia in March 2020, the pandemic has hit the economy hard, especially the Micro, Small, and Medium-sized Enterprises (MSMEs). This study aims to analyze MSMEs’ internal coping strategy to mitigate the impact of the pandemic, recovery strategy, and business transformation, as well as the needed government support to enable MSMEs to weather the crisis. Primary data was collected through a questionnaire administered to 2,535 MSMEs in 17 provinces. The results show that MSMEs’ coping strategy differs across firm size, sector, region, and owners’ gender. MSMEs also differ in their recovery path and medium-term business transformation in production, capital, marketing, and lines of business. Further, MSMEs require both financial and non-financial assistance, in addition to enabling the business environment to recover their businesses sustainably. The policy, academic and managerialimplications of the findings are provided.